Los creadores del vestido: los sastres de la Real Cámara en tiempos de Carlos IV y María Luisa de Parma (1789-1808) - Antúnez López, Sandra (Eikón / Imago, 2025)
The objective of this article focuses on knowing the artistic career of the main tailors during the reign of Charles IV and María Luisa de Parma. We will do a brief review of the situation of the tailors who worked for the palace, since they differed in their occupation, salary and position within the palatine hierarchy. We will analyze which dresses the queen ordered and by whom they were made. The artisan hands of the tailors Pedro Alcantara Garcia, Manuel Ballesteros, Jorge Martin and Francisco Gonzalez made the textile works intended for the feminine royal image. The primary sources consulted show previously unpublished data, which allow the study of clothing artisans and their textile production for the monarchy.